(untitled) (Revista Contexto & Educação, 2026)
Science teaching plays a crucial role in valuing scientific knowledge, particularly in the field of botany. Therefore, the use of the theme of medicinal plants becomes an option for meaningful learning, especially in Youth and Adult Education (EJA). In this context, the use of plants as a therapeutic resource reflects traditional knowledge transmitted over generations in a relevant way. This study conducted a systematic literature review aiming to identify pedagogical practices in the context of EJA that use medicinal plants in science teaching. The databases analyzed were Scopus, Web of Science, Scielo, and Google Scholar, resulting in a synthesis that highlighted several efficient learning approaches. The use of medicinal plants as a science teaching strategy in EJA presents significant potential for learning within the scope of botany teaching. The results showed that the use of medicinal plants as a didactic resource is based on their rich cultural history, highlighting the intersection between traditional knowledge and scientific knowledge. Furthermore, it values local biodiversity and explores scientific concepts through concrete examples. The bibliometric analysis also revealed that the most recurrent pedagogical practices in the studies were hands-on activities and visual exhibitions. Thus, the integration of medicinal plants in science teaching can be aligned with curricular content, exploring topics such as plant anatomy and physiology, chemistry of bioactive compounds and extraction processes, and the study of ethnic-racial relations.